An Exploration and Technical Notes for Advanced Airway Management on the Ski Slope: A Simulation Experiment - Peng Bai; Tian Xia; Zhongwei Yang; Wei Huai; Xiangyang Guo; Fang Zhou (Emergency Medicine International)
Background. Skiing is a high-risk winter sport, and the rate of injury fatality is the highest compared to other winter sports. During skiing rescue, the harsh natural environments will increase the difficulty of artificial airway establishment. There has been no research focusing on the establishment of the artificial airway during skiing rescue site. This study aims to simulate the real-world scenario, calculating and comparing the operation time of different artificial airways on the cold slope, and to explore the optimal method of establishing artificial airway on the cold slope, sharing our experience, technical notes, and pitfalls we encountered, hoping to help establish a standard operating procedure in advanced airway management on the ski slope. Methods. The simulated human was placed on the cold slope with the head under the feet. Artificial airway was established by the same anesthesiologist using endotracheal intubation (endotracheal intubation group), LMA Supreme laryngeal mask (LMA group), and I-gel laryngeal mask (I-gel group). Each method was repeated 5 times, and the operation time and whether it was successful by one attempt were recorded and compared between groups. Results. Three groups of artificial airway were successful by one attempt.. The bite block dropped and drifted away for one time in the endotracheal intubation group. Operation time is 209.2 ± 32.7 seconds in the endotracheal intubation group, 72.2 ± 3.1 seconds in the LMA group, and 52.6 ± 4.2 seconds in the I-gel group. ANOVA showed that there was a significant difference in the operation time among the three groups (p<0.001). Tukey’s post hoc test showed that there were statistically significant differences between the endotracheal intubation group and the other two groups in operation time, p<0.001, while there was no significant difference between the LMA group and I-gel group (p=0.275). Conclusion. The artificial airway can be completed by endotracheal intubation and LMA and I-gel laryngeal mask insertion on the cold slope. Artificial airway with the I-gel laryngeal mask takes the shortest time in this study. Extra caution should be paid to slippery and drifting.